Commodification of Mount Gede Pangrango National Park - Amri, K; Pungkas, A S (KnE Social Sciences, 2018)
Mount Gede Pangrango National Park (TNGGP) is an area of conservation administrator of natural resources and ecosystem located in Bogor, Cianjur, and Sukabumi District, West Java. One of its functions is the development and utilization of environmental service and natural tourism. Commodification of Mount Gede Pangrango was conducted by the government with the intention of increasing country’s income as well as maintaining natural preservation. Concomitant rise of technology and media, especially after the presence of ‘5 cm’ film and social-media activism, mountaineering activity has transformed into a popular activity resulting in a new meaning. Its implication is the emergence of new commodification conducted by several actors behind TNGGP with a capital accumulation motive in the end being to stabilize the new meaning of mountaineering activity. Those actors are private (agencies of mountaineering tourism, volunteer/ranger, product brand), local society, and government – that keep on negotiating and contesting in order to commodify the meaning of mountain and mountaineering activity. Then, what are new commodification forms conducted by those actors? How TNGGP is interpreted by those actors? And what are the kind of negotiation and contestation among them? Those questions will be answered in this article. The hypothesis is that each actor utilized power and access belonging to them in order to accumulate capital, both by commodifying TNGGP and the meaning of mountaineering activity by various ways. Each actor interprets TNGGP differently that has complex connection among them, but they rely on each other, and are profitable at once. This article is conducted by analysis qualitative descriptive method. Data are obtained through interview and engaged observation, including literature study and documentation of portal media. Keywords: Mount Gede Pangrango National Park, commodification, actor, negotiation, contestation